Central Venous Disease Increases the Risk of Microbial Colonization in Hemodialysis Catheters - Liang, Xianhui; Liu, Yamin; Chen, Bohan; Li, Ping; Zhao, Peixiang; Liu, Zhangsuo; Wang, Pei (Frontiers in Medicine, 2021)
Objectives Tunneled-cuffed catheters (TCCs) are widely used in maintenance hemodialysis patients. However, microbial colonization in catheters increases the likelihood of complications, such as catheter-related infection (CRI), catheter failure, hospitalization and death. Identification of the risk factors related to microorganism colonization may help us reduce these adverse events. Therefore, a retrospective analysis of patients who underwent TCC removal was conducted. Methods From 389 adult patients, 145 were selected for inclusion in the study. None of the patients met the diagnostic criteria for CRI within 30 days before recruitment. The right internal jugular vein was the unique route. The catheter removal procedure was guided by digital subtraction angiography. Catheter tips were collected for culture. Biochemical and clinical parameters were collected. Results The average age of this cohort was 55.46±17.25 years. A total of 45/145 (31.03%) patients were verified to have a positive catheter culture. The proportions of gram-positive bacteria, gram-negative bacteria and fungi were 57.8%, 28.9% and 13.3%, respectively. History of CRI (OR=2.44, 95% CI 1.09 to 5.49), fibrin sheath (OR=2.93, 95% CI 1.39 to 6.19), white blood cell (WBC) count ≥ 5.9×109/L (OR=2.31, 95% CI 1.12 to 4.77), moderate (OR=4.87, 95% CI 1.61 to 14.78) or severe central venous stenosis (CVS) (OR=4.74, 95% CI 1.16 to 19.38) and central venous thrombosis (CVT) (OR=3.41, 95% CI 1.51 to 7.69) were associated with a significantly increased incidence of microbial colonization in univariate analysis. Central venous disease (CVD) elevated the risk of microbial colonization, with an OR of 3.37 (1.47-7.71, P=0.004). Multivariate analysis showed that both CVS and CVT were associated with catheter microbial colonization, with ORs of 3.06 (1.20-7.78, P=0.019) and 4.13 (1.21-14.05, P=0.023), respectively. As the extent of stenosis increased, the relative risk of catheter microbial colonization also increased. In patients with moderate and severe stenosis, a sustained and significant increase in OR from 5.13 to 5.77 was observed. Conclusions An elevated WBC count and CVD can put hemodialysis patients with TCCs at a higher risk of microbial colonization, even if these patients do not have the relevant symptoms of infection. Avoiding indwelling catheters is still the primary method for preventing CRI.